Responsiveness to change of The Malay-Ecohis following treatment of early childhood caries under general anaesthesia / Nor Azlina Hashim - Nor Azlina, Hashim (2017)
Background: Oral health-related quality of life (OHRQoL) measures should be tested for their sensitivity and responsiveness to changes in OHRQoL if they are to be used as outcome measures in clinical interventions. Objectives: (a) To evaluate the sensitivity of the Malay version of Early Childhood Oral Health Impact Scale (Malay-ECOHIS) to dental treatment of early childhood caries (ECC) under General Anesthesia (GA) by: (i) assessing changes in the distribution of Malay-ECOHIS scores before and after treatment under GA, (ii) assessing the association between Malay-ECOHIS change scores and severity of decayed teeth (dt) categorized by the median and percentile score, (iii) assessing the correlation between Malay-ECOHIS change scores and the number of decayed teeth, and (iv) assessing the correlation between Malay-ECOHIS change scores and number of extracted teeth; (b) evaluate the responsiveness of the Malay-ECOHIS to dental treatment of ECC under GA by comparing whether the observed changes in Malay-ECOHIS scores and effect size (ES) took the form of a gradient across the global transition judgement; and (c) establish the Minimal Important Difference (MID) of the Malay-ECOHIS. Methods: A consecutive sample of parents of 158 preschool children (aged 6 and younger) with ECC attending five public hospitals in Selangor for dental treatment under GA was recruited over an 8-month period. Parents self-completed the Malay-ECOHIS prior to and 4 weeks following their child’s dental treatment. In addition, parents answered a global health transition judgement concerning the change in their child’s overall oral health condition compared to before treatment. Data were analyzed using independent and paired samples T-test, ANOVA, Pearson correlation, and standardised scores. Results: Overall, 138 children completed the study with response rate of 87.3%. The final sample comprised parents of 76 male (55.1%) and 62 female (44.9%) preschool children with mean age of 4.54 years (SD=1.01). The ECOHIS mean score after treatment was significantly lower compared to before treatment. This significant reduction in mean score existed for total Malay-ECOHIS, Child Impact Section (CIS), Family Impact Section (FIS), and all the sub-domains, respectively (P<0.001). The magnitude of change (ES) of total Malay-ECOHIS following treatment was +1.0 and among domains ranged from +0.4 to +1.9. There was no significant association between Malay-ECOHIS change scores and severity of decayed teeth (dt) categorized by median or percentile score. However, there was a weak, positive correlation between number of decayed teeth (dt) and Malay-ECOHIS (r=0.165, p=0.05) and CIS change scores (r=0.175, p<0.05), respectively. No significant correlation was found between Malay-ECOHIS change scores and number of extracted teeth. Based on global health transition judgement, 62.3% of parents reported their child’s oral condition “a little improved” while 37.7% reported “much improved” following treatment under GA with ECOHIS mean change score of 6.7 (ES=+1.1) and 9.6 (ES=+1.2), respectively. There was an observed gradient in the changes of Malay-ECOHIS scores and effect sizes in relation to global health transition judgement of oral change following treatment, supporting the responsiveness of the measure. The Malay-ECOHIS MID was found to be 7-point change with large ES of +1.0. Conclusion: The Malay-ECOHIS is empirically proven to be sensitive and responsiveness to dental treatment of ECC under GA.